The Role of The Sociology Teacher in Implementing Character Education - Akhiruddin; Monika Wattimena; Andi Nursida; Salehuddin; Ridwan (CV. Eureka Murakabi Abadi, 2022)
The aim of the research is to analyze the role of sociology teachers in implementing character education through learning at school of Makassar. This type of research used descriptive qualitative research namely to analyze solutions to existing problems based on data, presenting data, analyzing and interpreting. Research informants were determined by purposive sampling technique consisting of the principal (curriculum section), Sociology teachers in grades X, XI, XII, and students who were registered as social studies students. Data collection techniques were observation, interviews and documentation. Data analysis techniques were data use, data reduction, data presentation and conclusion.The results showed that the role of the sociology teacher in implementing character education through learning was as follows; Inserting moral messages in learning that are associated with learning materials, Linking the material with social phenomena that exist in society, Applying learning models that can foster a sense of empathy, and responsibility, Providing exemplary for students such as arriving on time, not smoking, throwing trash in its place and caring for others, Cooperating with guidance counseling and students' parents. As conclusion that character education can be implemented through learning in schools and sociology teachers have role in implementing character education.